MAKᾹNAT AL-ADYᾹN GHAIR AL-ISLᾹMIYYAH MIN AL-MANẒŪR AL-QUR’ᾹNῙ: Dirāsah Tafsīriyah Siyāqiyah - Abad Badruzaman (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
he problem is that not every religious believer is willing to live side by side with other people who are different. This phenomenon gives rise to clashes, hostility, and tensions between adherents of different religions. The main reason mostly refers to the interpretation with a narrow perspective on several religious texts, especially with the existence of verses that emphasize the exclusivity of eschatological happiness and the limitation of the right of exclusivity to certain groups. Through the contextual exegesis approach and the data analyzed by the thematic framework, this paper aims to present an idea of the response of the Quran to non-Islamic religions. The author also tries to interpret the verses of the Quran that show exclusivity and exclusive truth in a direction that is in accordance with other verses that call for tolerance and openness, starting with the contextual approach commonly used in the field of Quranic interpretation's studies today. The writer hopes that this paper will contribute academically to answer the stagnation of interpretation's phenomenon experienced by most religious communities in the modern era. Particularly, this contribution becomes an encouragement to build healthy relationships filled with love, compassion, to maintain humanity and respect for others, to safeguard rights, and to achieve shared human values and noble goals among others.